Conservation genetics of the world's most endangered seabird, the Chatham Island tāiko (Pterodroma magentae) : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Molecular Biosciences at Massey University, Auckland, New Zealand - Lawrence, Hayley Ann (Massey University, 2008)
The research field of genetics provides useful tools to investigate the biology of species that are difficult to observe and study and are especially valuable in guiding the conservation of endangered species. The Chatham Island Tāiko (Tchāik, Pterodroma magentae) is the world’s most endangered seabird with an estimated population size of just 120-150 birds, including only 8-15 breeding pairs. This thesis used genetic techniques to investigate aspects of Tāiko biology and relationships in order to aid Tāiko conservation. The mitochondrial cytochrome b gene and duplicated regions of domain I of the mitochondrial control region were DNA sequenced in almost the entire known Tāiko population. The level of genetic variation revealed in Tāiko was unexpectedly high considering endangered species typically exhibit low genetic diversity. Sequencing of ancient DNA from subfossil Tāiko bones allowed an investigation of the past level of genetic variation and the species’ previous geographic distribution. A large proportion of the genetic diversity of the extinct Tāiko populations was retained in the remnant population. However, genetic variation in Tāiko chicks was low, thus genetic diversity in the population could be lost in just a few generations. There are many nonbreeding Tāiko so DNA sexing was used to examine sex ratios in the population. Almost all unpaired birds were male, which signified a potential Allee effect (i.e. that a reduced density of potential mates is decreasing population productivity). Further understanding of the Tāiko mating system and behaviour was obtained by parentage, sibship and pairwise relatedness analyses of genotypes at eight microsatellite DNA loci. It is important that Tāiko are found so they can be protected from introduced predators. The results of mitochondrial DNA sequencing and microsatellite DNA genotyping indicated that there are likely to be more Tāiko breeding in undiscovered areas. Analysis of philopatry using both mitochondrial and nuclear markers can assist conservation by the identification of areas to search for these undiscovered individuals. Tāiko may have once and could still be found on islands near South America since DNA sequencing showed the Magenta Petrel type specimen (collected in 1867 in the South Pacific Ocean) is a Tāiko.
Hokopapa o tch tchāik
Whakapapa o te tāiko
Keywords: Chatham Island taiko; Endangered species; Conservation; Genetic variation; Pterodroma magentae; Magenta petrel; Endangered birds; Fields of Research::270000 Biological Sciences::270200 Genetics::270203 Population and ecological genetics